Perbedaan Model Problem Based Learning dan Discovery Learning Ditinjau Dari Hasil Belajar Matematika Siswa Kelas 4 SD - Bella Anandya Yovita Oktaviani; Mawardi Mawardi; Suhandi Astuti (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
The purpose of this study is to determine differences in learning outcomes of 4th grade students in Mathematics in SD Gugus Patimura using Problem-based Learning and Discovery Learning model. This is a quasi experimental research. The instrument of data collection was test items, previously tested of its validity and reliability. The result of hypothesis test using ANCOVA test showed the result of significance / probability 0,00 <0,05, meaning H0 was refused and Ha was accepted. It means that Problem-based Learning has significantly higher impact than Discovery Learning model. The conclusion is supported by the average value of the learning outcomes using Problem-based Learning model which was 80.24, while the one using Discovery Learnings model only reached 71,87. Based on the conclusions of this study, it is recommended that the elementary school teachers use the model of learning Problem Based Learning.